2016
DOI: 10.1002/anie.201600428
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Radiative Energy Transfer Mediated by Hybrid Light‐Matter States

Abstract: We present direct evidence of enhanced non-radiative energy transfer between two J-aggregated cyanine dyes strongly coupled to the vacuum field of a cavity. Excitation spectroscopy and femtosecond pump-probe measurements show that the energy transfer is highly efficient when both the donor and acceptor form light-matter hybrid states with the vacuum field. The rate of energy transfer is increased by a factor of seven under those conditions as compared to the normal situation outside the cavity, with a correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
200
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(217 citation statements)
references
References 32 publications
7
200
2
Order By: Relevance
“…Polaritons can thus entangle cyanine dyes at a distance. Studies of the transient absorption dynamics of donor–acceptor systems also showed the modification of the non‐radiative transfers in the cavity . It should be pointed out that the energy transfer becomes independent of distance as long as strong coupling is maintained which is in the good agreement with a theoretical prediction .…”
Section: Strong Coupling Applicationssupporting
confidence: 66%
“…Polaritons can thus entangle cyanine dyes at a distance. Studies of the transient absorption dynamics of donor–acceptor systems also showed the modification of the non‐radiative transfers in the cavity . It should be pointed out that the energy transfer becomes independent of distance as long as strong coupling is maintained which is in the good agreement with a theoretical prediction .…”
Section: Strong Coupling Applicationssupporting
confidence: 66%
“…This is very much like when the donor and acceptor are chemically linked with an overlap of their wave functions. [7] We reported that the rate of nonradiative energy transfer was increased by af actor of seven under those conditions as compared to the normal situation outside the cavity,w ith ac orresponding effect on the energy transfer efficiency. [7] Such cascaded strongly coupled systems lead to the intriguing possibility of achieving energy transfer of spatially separated but entangled donors and acceptors over distances where Fçrster type mechanism is no longer possible as illustrated in Figure 1b.Itshould be recalled that Fçrster type energy transfer rate k ET is proportional to 1 R 6 DA where R DA is the average donor-acceptor distance and it is well established that energy transfer is highly unlikely for R DA !…”
mentioning
confidence: 88%
“…This is typically achieved by placing the quantum emitters in ar esonant cavity.A nother way to modify energy transfer is under strong light-matter coupling as recently demonstrated. [7,8] In those experiments,b oth the donor Da nd the acceptor Awere coupled to ac avity,l eading to ac ascade of hybrid light-matter or polaritonic states as illustrated in Figure 1a.T he three new hybrid states,n amely the upper (UP), middle (MP) and lower (LP) polaritonic states are quantum mechanically entangled and provide an effective path for energy transfer. This is very much like when the donor and acceptor are chemically linked with an overlap of their wave functions.…”
mentioning
confidence: 99%
“…In the limit in which multiple excitonic states can each separately enter the strong-coupling regime, hybrid polariton states form that are a mixture of the cavity photon and the different excitonic components. Such 'hybrid' states can be used to mediate rapid and efficient energy transfer over extremely long distances through the highly delocalised photon component, and have been proposed as model systems in which energy transfer in lightharvesting systems may be explored [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of modified energy relaxation has been clearly demonstrated in the case of distinct J-aggregates [19,20], but is of greater interest in light-harvesting systems such as the archetypal photosynthetic complexes [21]. It has already been shown that the primary component of these complexes -chlorophylls -is capable of strong coupling [18].…”
Section: Introductionmentioning
confidence: 99%